Controlling Extra- and Intramacrophagic Mycobacterium abscessus by Targeting Mycolic Acid Transport - Viljoen, Albertus; Herrmann, Jean-Louis; Onajole, Oluseye K.; Stec, Jozef; Kozikowski, Alan P.; Kremer, Laurent (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium abscessus is a rapidly growing mycobacterium (RGM) causing serious infections especially among cystic fibrosis patients. Extremely limited therapeutic options against M. abscessus and a rise in infections with this mycobacterium require novel chemotherapies and a better understanding of how the bacterium causes infection. Different from most RGM, M. abscessus can survive inside macrophages and persist for long durations in infected tissues. We recently delineated differences in the infective programs followed by smooth (S) and rough (R) variants of M. abscessus. Unexpectedly, we found that the S variant behaves like pathogenic slow growing mycobacteria, through maintaining a block on the phagosome maturation process and by inducing phagosome-cytosol communications. On the other hand, R variant infection triggers autophagy and apoptosis, reminiscent of the way that macrophages control RGM. However, the R variant has an exquisite capacity to form extracellular cords, allowing these bacteria to rapidly divide and evade phagocytosis. Therefore, new chemotherapeutic interventions against M. abscessus need to efficiently deal with both the reservoir of intracellular bacilli and the extracellular cords. In this context, we recently identified two chemical entities that were very effective against both M. abscessus populations. Although being structurally unrelated these two chemotypes inhibit the activity of the essential mycolic acid transporter, MmpL3. In this Perspective, we aimed to highlight recent insights into how M. abscessus interacts with phagocytic cells and how the inhibition of mycolic acid transport in this pathogenic RGM could be an efficient means to control both intracellular and extracellular populations of the bacterium.